Penetrating Aortic Ulcer in an Elderly Female: An Important Consideration in Chest Pain Presentations - Snels, Nicholas (Archives of Clinical and Medical Case Reports, 2019)
Introduction: Chest pain is one of the most common presenting complaints to emergency departments. Recent advances in imaging have allowed greater definition of acute aortic syndromes, a collection of diseases, including aortic dissections in addition to rarer aortic ulceration and intramural thrombus. Herein I present a case of a lady with chest pain caused by a penetrating aortic ulcer. Case Report: A 74 year old female presented with central chest pain of four days duration on a background significant for hypertension, smoking and a family history of vasculopathy. Physical examination followed by radiological investigations revealed a penetrating aortic ulcer in the ascending aorta. The patient was referred to the vascular team who managed her conservatively with antihypertensives. Conclusion: These are many causes for acute onset chest pain. Aortic arch ulceration is a rare cause, however remains for consideration in working these patients up given the possibility to lead to aortic rupture.